1990
DOI: 10.1016/s0006-3495(90)82562-5
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization and conformation change in solutions of calf lens gamma II-crystallin. Results from 1/T1 nuclear magnetic relaxation dispersion profiles

Abstract: From analyses of the magnetic field dependence of 1/T1 (nuclear magnetic relaxation dispersion [NMRD] profiles) of water protons in solutions of highly purified calf lens gamma II-crystallin, we find that monomers form oligomers at relatively low concentrations, which increase in size with increasing concentration and decreasing temperature. At approximately 16% by volume and -4 degrees C, the mean oligomeric molecular weight is approximately 120-fold greater than the monomeric value of 20 kD. Below this conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…We can conclude that there is a temperature-induced aggregation or temporal associations but we cannot quantify them. Recently, Koenig et al found that 7-crystallin fractions aggregate as the temperature decreases (Koenig et a]., 1990(Koenig et a]., , 1992. They claim that the phase transition observed in y-crystallin solutions is driven by the formation of these protein aggregates.…”
Section: Second Virial Coefficient Results a Debye Plot [A Plot Of Rmentioning
confidence: 99%
“…We can conclude that there is a temperature-induced aggregation or temporal associations but we cannot quantify them. Recently, Koenig et al found that 7-crystallin fractions aggregate as the temperature decreases (Koenig et a]., 1990(Koenig et a]., , 1992. They claim that the phase transition observed in y-crystallin solutions is driven by the formation of these protein aggregates.…”
Section: Second Virial Coefficient Results a Debye Plot [A Plot Of Rmentioning
confidence: 99%
“…Here, we use 1 H MRD to determine the rotational correlation times (or rotational diffusion coefficients) of the oligomeric species present in solution. Whereas MRD has been used in a few earlier studies of protein selfassociation (Lindstrom et al, 1976;Raeymaekers et al, 1989;Koenig et al, 1990), our data extend to higher frequencies (necessary for a small protein like BPTI) and are analyzed in a more rigorous way (Halle et al, 1998).…”
Section: Introductionmentioning
confidence: 87%